EXPLORING CLASS IX STUDENTS' LANGUAGE NEEDS AND PREFERENCES IN A CLIL CONTEXT: A COMPREHENSIVE NEEDS ANALYSIS - Dandu, Harish; Pugazh, A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study's significance lies in the evolving global education landscape facing technological, social, and economic challenges. Students’ motivation, self-esteem, and individuality are vital in learning a language. India's fluctuating English proficiency highlights the need for improved language skills for international opportunities. Addressing language learning challenges necessitates effective methodologies like Content and Language Integrated Learning (CLIL), aligning with the changing educational paradigm. The need analysis conducted among class-IX students revealed their positive attitude towards learning English, acknowledging its significance for future academic and career prospects. They expressed interest in using English for internet browsing and communication with people from diverse linguistic backgrounds. However, limited language exposure outside the classroom and modest family support were noted as challenges.